What a Social Security, Work Discipline, and Organisational Commitment affect Employee Productivity - Faizah, Erna Nur; Hakim, Adi Lukman; Basyah, Muh Ali (Jurnal Ekobismen, 2025)
Companies are very concerned about human resource management, management systems, and work productivity. Employees with good work productivity are employees who can improve the quality and quantity of work formed in a company. This study aims to partially determine the effect of social security, work discipline and organizational commitment on work productivity and to determine the simultaneous effect of social security, work discipline and organizational commitment on work productivity at the company PT Nongguan Biotek Indonesia. This research uses quantitative and descriptive methods.  In this study, 40 respondents from the population were taken. The data analysis technique used in the study was multiple linear regression analysis. Based on the results of the study, it shows that partially social security, work discipline and organisational commitment have a positive and significant effect on work productivity, organisational commitment has a positive and significant effect on work productivity, and work discipline and organisational commitment have a positive and significant effect together on work productivity